Synthesis of N-functionalized 2,3-disubstituted benzofurans/naphthofurans from para-quinone methides and isocyanides via the [4+1] annulation pathway - Kale, Someshwar B.; Kumar, Manish; Shinde, Dinesh R.; Krishna, Gamidi Rama; Das, Utpal (Organic Chemistry Frontiers, 2023)
A scandium triflate catalyzed [4 + 1] cycloaddition reaction of 2-hydroxy-substituted para-quinone methides and isocyanides has been developed. This operationally simple, efficient and practical protocol provides straightforward access to a variety of N-functionalized 2,3-disubstituted benzofuran/naphthofuran derivatives with broad functional group compatibility and good scalability.

Synthesis of benzannulated [5,6] oxa-fused/spiro-lactones via [4+2] cycloaddition with quinone methides: new insights into deconjugated butenolide reactivity - Kumar, Manish; Kale, Someshwar B.; Jawahar, Subramani; Barkade, Apurva D.; Das, Utpal (Journal of Organic Chemistry, 2025)
In this study, we unfold a Lewis-acid-catalyzed inverse electron demand hetero Diels-Alder (IEDHDA) [4 + 2] reaction, leveraging the unique beta-selective nucleophilicity of deconjugate lactone in conjunction with quinone methides for the synthesis of polycyclic fused and spiro acetals in a one-pot process. This cascade annulation reaction efficiently generates 3/4 chiral centers with high diastereoselectivity. The developed methodology proceeds under mild reaction conditions and exhibits a broad substrate scope for fused and spiro acetal formation.